2011
DOI: 10.1007/s00146-011-0332-8
|View full text |Cite
|
Sign up to set email alerts
|

Granularity in reciprocity

Abstract: Witnessing in merging biological, social and algorithmic realities is crucial to trust, as modelled in the YUTPA framework. Being witness and bearing witness is fundamental to human interaction. System participation in human communities of practice challenges the notion of witnessing and therefore the ability to build trust. Nevertheless, through trial and error, people in a variety of practices have found ways to establish the presence and develop trust in merging realities. This paper presents the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This paper distinguishes 6 dimensions ( Figure 2) of engagement adopted by KM studies:  Interaction: level of participant engagement in the knowledge exchange regarding to perceived costs and benefits (Cyr and Wei Choo, 2010).  Presence: level of participants' presence in relation to time, place, actions and relations (Nevejan and Brazier, 2012;Riva et al, 2011).  Enactment: level of participants' engagement in legislation and self-regulation in the governance of KM systems (Tseng and Kuo, 2014).…”
Section: Research Modelmentioning
confidence: 99%
“…This paper distinguishes 6 dimensions ( Figure 2) of engagement adopted by KM studies:  Interaction: level of participant engagement in the knowledge exchange regarding to perceived costs and benefits (Cyr and Wei Choo, 2010).  Presence: level of participants' presence in relation to time, place, actions and relations (Nevejan and Brazier, 2012;Riva et al, 2011).  Enactment: level of participants' engagement in legislation and self-regulation in the governance of KM systems (Tseng and Kuo, 2014).…”
Section: Research Modelmentioning
confidence: 99%
“…The YUTPA dimensions resonate well with the need to acquire insight into the physical (dimensions place and time) and social (dimensions relation and action) structure of and networks within Bouwlust. This framework has also been used in other settings (e.g., Nevejan and Brazier, 2012) to understand the design space for participation. In Bouwlust, the YUTPA analysis, for example, revealed that there are many green areas, such as small parks and playgrounds, but that those are rarely used.…”
Section: Artistic Researchmentioning
confidence: 99%
“…In a specific situation, a factor has specific values. The values are determined in discussions with stakeholders by posing questions on the importance and value of each factor in specific situations [4]. As a result, trade-offs for establishing trust are translated into design requirements, in this case for SamenMarkt ® [5].…”
Section: Analysing the Current Crisis Using The Yutpa Framework For Imentioning
confidence: 99%